Antibacterial Effect Of Curcuma Domestica Ethanolic Extract On Group A Streptococcus Î’ Hemoyticus - Halim, Stefan W; Wihanto, Laura; Sutandhio, Silvia (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction : Pharyngitis is one of the most common infection that general practitioners handled. It is estimated in one year there are 15 million people with pharyngitis will come to the doctor. American Society of Microbiology said that 94,3 % from 402 patient who were suspected pharyngitis received antibiotic therapy even without indication of antibiotic therapy. Antibiotic resistance is becoming a great threat for the world today. World Health Organization state that one of the plan to fight antibiotic resistance is to research and develop new drugs. Curcuma domestica is a plant that is widely used in Indonesia and some research said that it has anti-inflammatory, antioxidant, and antimicrobial effect. Aim: The aim of this study is to find the antibacterial effect of Curcuma domestica ethanolic extract on Group A Streptococcus ? hemolyticus and find the Minimum Bactericidal Concentration (MBC) value. Methods : This was in vitro experimental study with broth microdilution method and inoculation on agar blood media to find the MBC. Treatment group consisting of, media (Mueller Hinton Blood Broth), Group A Streptococcus ? hemolyticus bacteria, and 5 concentrations (312.5 ?g/ml, 625 ?g/ml, 1250 ?g/ml, 2500 ?g/ml, 5000 ?g/ml) of Curcuma domestica extract. Result : There is no bacterial growth at 5000 ?g/ml concentration on solid media, but there are less bacterial growth at 2500 ?g/ml than at concentration 312.5 ?g/ml, 625 ?g/ml, 1250 ?g/ml. Conclusion: There is an antibacterial effect of Curcuma domestica ethanolic extract on Group A Streptococcus ? hemolyticus with MBC value in range 2500 ? 5000 ?g/ml.